NURSING SCIENCE STUDY PROGRAM STUDENTS’ PERCEPTION TOWARD THE USE OF EDMODO AS SUPPLEMENTARY TOOL IN LEARNING ENGLISH II AT STIK BINA HUSADA PALEMBANG 2019/2020 - Agus Wahyudi (Language and Education Journal, 2019)
Due to the rapid advancement of technology, teachers are expected to integrate technology into the classroom to engage students who are considered as digital-natives. Thus, Edmodo as online learning platform is widely used by English teachers in teaching and learning. The online learning platforms are also used as a supplementary tool to promote independent learning. Edmodo is primarily a tool for within-class communication which provides several ways for teachers to connect with other teachers. This research focused on students’ perspective of the use of Edmodo as a supplementary tool in learning English. The researcher used triangulation approach in gathering data and survey questionnaire adapted from Enriquez (2014) used as the main research instrument. Forty four students joined the Edmodo class and filled the questionnaire completely. The results showed on the statement regarding the usefulness of reference materials posted by the teacher in Edmodo, a significant number 66.8% agree and 33.20% strongly agree or considered the reference materials as vital in understanding the course better. Participants also perceived that Edmodo is a good learning tool to supplement face to face discussion. One disadvantage in using Edmodo as perceived by 19.4% of the participants is the difficult procedure to understand and to follow for them. Overall, the findings affirmed that majority of the participants considered it as an effective supplementary tool in learning English